A full order sliding mode tracking controller design for an electrohydraulic control system - Ngadengon@Ngadungon, Rafidah (2005)
Electrohydraulic control system are widely use in industry due to continuous operation, higher speed of response with fast motion etc. However, there is a drawback that it is difficult to control because of the highly nonlinear and parameters uncertainties. In this project, a Full Order Sliding Mode Controller is design to control the system. First, the mathematical model of the electrohydraulic servo control system is developed. Then the mathematic model will be transformed into state space representation for the purposed of designing the controller. The system will be treated as an uncertain system with bounded uncertainties where the bounded are assumed known. The proposed controller will be designed based on deterministic approach, such that the overall system is practically stable and tracks the desired trajectory in spite the uncertainties and nonlinearities present in the system. The performance and reliability of the proposal controller will be determined by performing extensive simulation using MATLAB/SIMULINK. Lastly, the performance of the controller is to be compared with Independent Joint Linear Control and advanced deterministic controller.